Typical Research-Based Learning Approach in Improving Al-Quran Interpretation in Higher Education - Mahyuddin Barni (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
This review was review the typical research-based learning (RBL) approach in conducting surface interpretation in higher education. We believe the RBL approach is applied in general sciences and may be used in learning the Alquran room as a tool to understand specific lesson contexts. Therefore, we have reviewed many data sources from different databases searching electronically. The sources are publications for academic works such as journals, books, and websites. We analyzed that literature using a simple review approach such as coding system, interpretation, and taking conclusion to answer the question validly. After discussing the result, we may conclude that learning took by using multiple resources of the Koran that served in many different materials, texts, audio, to understand the meaning and relevance, questions, and even challenging text. Students organize, evaluate, and synthesize information and ideas as they construct the Qur’an text and signs. Keywords: Research-Based Learning Approach, Al Quran Interpretation, Research-Based Learning (RBL)